2021
DOI: 10.1111/jav.02673
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory effect of egg size dimorphism on hatching asynchrony in Magellanic penguin

Abstract: Egg laying is one of the most important phases in a female bird's breeding cycle. Its cost is high because eggs contain all the resources needed for the development of an embryo. Variation in size and quality of eggs can have important long-term consequences for offspring survival. Hatching asynchrony is known to influence sibling competition in many bird species. Last-hatched chicks will have a competitive disadvantage throughout the pre-fledgling period because they are smaller. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…In this species, body condition of males may cause effects between siblings (Marchisio et al 2021). We found that improving males body condition leads to a detriment in the growth rate of chicks on the season of high breeding success.…”
Section: Discussionmentioning
confidence: 71%
“…In this species, body condition of males may cause effects between siblings (Marchisio et al 2021). We found that improving males body condition leads to a detriment in the growth rate of chicks on the season of high breeding success.…”
Section: Discussionmentioning
confidence: 71%